TRADISI PERAYAAN KENDURI MAULID NABI DI ACEH BESAR (Jurnal Adabiya, 2020)
The Prophet's Birthday celebration is a tradition carried out by the Acehnese people in commemoration of the birth of the Great Prophet Muhammad Saw. In Aceh something generally celebrated is usually done with kenduri (food). The results of this study indicate that the Kenduri Maulid (Khanduri Maulod) can be carried out in three months, starting from the month of early Rabiul, Late Rabiul, and Early Jumadil. Selected one of the days between the three months to celebrate the feast of maulid. Each village or village has its own characteristics in the celebration of the feather maulid, both in the form of celebrations or food menus. The hallmark of the maidid feast in Aceh Besar is marked by the existence of the main dish of Kuah Beulangong. According to the Acehnese glorifying the birthday of the Prophet by means of large-scale calms is a must for those who are able, as a form of gratitude for the blessings of faith, Islam and ihsan that have been obtained.
Keywords: Maulid; Tradition; Kenduri; Aceh Besar